Anti-Cancer Potential of Linear β-(1→6)-D-Glucan from Agaricus bisporus on Estrogen Receptor-Positive (ER+) Breast Cancer Cells - Renata Rutckeviski; Claudia Rita Corso; Aline Simoneti Fonseca; Mariane Londero Rodrigues; Yony Román-Ochoa; Thales Ricardo Cipriani; Luciane Regina Cavalli; Silvia Maria Suter Correia Cadena; Fhernanda Ribeiro Smiderle (Molecules, 2024)
Mushroom β-D-glucans can be isolated from several species, including the widely consumed Agaricus bisporus. Besides immunomodulatory responses, some β-D-glucans may exhibit direct antitumoral effects. It was previously observed that a β-(1→6)-D-glucan (BDG16) has indirect cytotoxicity on triple-negative breast cancer cells. In this study, the cytotoxicity of this same glucan was observed on estrogen receptor-positive (ER+) breast cancer cells (MCF-7). Cell viability was determined by multiple methods to assess metabolic activity, lysosomal membrane integrity, and adhesion capacity. Assays to evaluate cell respiration, cell cycle, apoptosis, necroptosis, and oxidative stress were performed to determine the action of BDG16 on MCF-7 cells. A gradual and significant cell viability reduction was observed when the cells were treated with BDG16 (10–1000 µg/mL). This result could be associated with the inhibition of the basal state respiration after incubation with the β-D-glucan. The cells showed a significant arrest in G1 phase population at 1000 µg/mL, with no induction of apoptosis. However, an increase in necrosis and necroptosis at the same concentration was observed. No difference in oxidative stress-related molecules was observed. Altogether, our findings demonstrate that BDG16 directly induces toxicity in MCF-7 cells, primarily by impairing mitochondrial respiration and promoting necroptosis. The specific mechanisms that mediate this action are being investigated.